Edukasi Pembuatan Media Pembelajaran Audio-Visual Berupa Worksheet QR Code Menggunakan Aplikasi Canva dan Vocaroo di TK Mentari Purwakarta - Siti Raihani Sholehah; Ai Rahmawati; Sumayah Nabila; Ida Rahmawati; Finita Dewi; Anuncius Gumawang Jati (Universitas Pendidikan Indonesia Kampus Purwakarta, 2023)
In this era of globalization, technology plays an important role in various fields, one of which is in the field of education. Being a teacher in this era is required to have competencies that are in accordance with learning in the 21st century. However, it cannot be denied that in reality there are still many teachers who do not know how to operate learning using digital technology, one of which is making learning media using digital technology. Learning using media will increase teacher creativity and make it easier to convey teaching material so that it can be conveyed to students appropriately and more effectively. Through educating teachers by creating a QR code worksheet using the Canva and Vocaroo applications as audio-visual learning media at Mentari Kindergarten will be one of the solutions to problems. The result of this activity is that teachers can find out how to use the Canva and Vocaroo Applications. Furthermore, by holding this training, teachers can express their ideas and creativity in making QR code worksheets, this shows that the evidence of this training activity has been carried out. The huge impact of education for teachers in making QR code worksheet learning media using the Canva and Vocaroo applications makes teachers creative and innovative. Through learning media, an attractive QR code worksheet will increase students' interest in learning.